Construction of Functionalized Azapolycyclic Architectures via Formal Amide Insertion at a Low Catalyst Loading of Copper Trifluoroacetylacetonate. Issue 19 (31st August 2016) - Harada, Shingo; Kato, Ryosuke; Nemoto, Tetsuhiro
Abstract: A formal amide insertion reaction for the synthesis of nitrogen‐bridged polycyclic frameworks with diverse functionalities was developed using a sustainable copper catalyst as an advantageous alternative to precious rhodium catalysts. The remarkable feature of this methodology is the amount of catalyst loading (0.05 mol%). The optimized reaction conditions enable access to aromatic ring‐fused 8‐azabicyclo[3.2.1]octane, 9‐azabicyclo[3.3.1]nonane, and 6‐azabicyclo[3.2.2]nonane derivatives in moderate to excellent yields. Abstract :